PENGGUNAAN N,O-KARBOKSIMETIL KITOSAN UNTUK MEMPERPANJANG UMUR SIMPAN BAKSO IKAN PATIN PADA SUHU KAMAR - , SINTA DWI C ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this research is to know N,O-Carboxymethyl Chitosan influenced to extend shelf life of catfish fishballs and to know the best N,O-Carboxymethyl chitosan concentration to extend shelf life of catfish fishballs. The stages of this research was divided into preliminary research and main research. The preliminary research were (1) infrared spectra analyses of chitosan, (2) measurememt of deacetilation degree, (3) Production of N,O-Carboxymethyl Chitosan, (4) infrared spectra analyses of N,O- Carboxymethyl Chitosan, (5) yield test, (6) solubility test, and (7) Minimum Inhibitory Consentration (MIC) test. The result of Minimum Inhibitory Consentration (MIC) test was used to determine the concentration of N,O-Carboxymethyl Chitosan in main research. The fishballs was submerged into N,O-Carboxymethyl Chitosan solution at the concentration of 0%, 0,5%, 1%, 1,5%, 2%, and 2,5% for 60 minutes. The fishball were measured for the parameter of (1) pH, (2) organoleptic, (3) Total Plate Count (TPC), (4) moisture content, (5) ash content, (6) protein content, (7) fat content, and (8) hedonic value. The result of organoleptic test showed that catfish fishballs without N,O- Carboxymethyl Chitosan stored at room temperature spoiled in 24 hours. Whereas catfish fishballs with 1%